Validación de una metodología adaptada para la identificación de conexiones pluviales ilícitas al alcantarillado sanitariode la ESPH - Rivera-Dobles, Daniela (Instituto Tecnológico de Costa Rica, 2014)
Illicit storm waterconnections to storm sewer cause overloadof the sewage system and wastewater treatment plant (WWTP) of the Public Service Company of Heredia (ESPH), which 9 contaminates the city and causes dumping of untreated wastewater into rivers. Methodology adapted from TheCenter of Watershed Protection andthe U.S. Environmental Protection Agency (EPA)program for identification and elimination of these connections and their implementation in two communities in the province of Heredia is presented in this study. Evaluating the state of the sewage system, the characteristics of the zones and the material in hand it was reached to the decision to apply the Dye Test in the downspouts of the constructions, checking if the dye came out through the storm or sanitary network. The pilot study covered an area of 214 077 m2 and 27 139 customers of the population with sanitary sewer service of the ESPH. The document with the methodology for identification of illicit stormwater connections was generated, illegal connections in the area were identified and evaluated, and the effectiveness and possible improvements of the validated methodology were also analyzed. It was obtained that 64 % of households with illegal connections were in Los Lagos, residential sector and 36% in Heredia Centro. In total, 18% of the population evaluated was identified with illicit connections. It wasn’t possible to assess a 12.5 % of the population. Initial affordable monthly budget of ¢ 161,875 and ¢ 1,593,393 (Exchange rate $1 USD = 540.19 for March 21st, 2014)would be required to carry out the project in bigger extend.It is recommended to carry out a pilot project in a more representative sample to be able to analyze the real environmental impact of illicit connections.
Proyecto de Graduación ( Licenciatura en Ingeniería Ambiental) Instituto Tecnológico de Costa Rica, Escuela de Química, 2014.
Keywords: Sistema de alcantarillado; Servicios públicos; Plantas de tratamientos de aguas residuales; Manejo de cuencas; Impacto ambiental